The economic burden of schizophrenia in Malaysia - Teoh SL; Chong HY; Abdul Aziz S; Chemi N; Othman AR; Md Zaki N; Vanichkulpitak P; Chaiyakunapruk N (Neuropsychiatric Disease and Treatment, 2017)
Siew Li Teoh,1 Huey Yi Chong,1 Salina Abdul Aziz,2 Norliza Chemi,2 Abdul Razak Othman,2 Nurzuriana Md Zaki,2 Possatorn Vanichkulpitak,3 Nathorn Chaiyakunapruk1,4–6 1School of Pharmacy, Monash University Malaysia, Selangor, 2Department of Psychiatry and Mental Health, Hospital Kuala Lumpur, Kuala Lumpur, Malaysia; 3Faculty of Pharmacy, Silpakorn University, Nakhon Pathom, 4Center of Pharmaceutical Outcomes Research (CPOR), Department of Pharmacy Practice, Faculty of Pharmaceutical Sciences, Naresuan University, Phitsanulok, Thailand; 5School of Pharmacy, University of Wisconsin, Madison, WI, USA; 6Health and Well-being Cluster, Global Asia in the 21st Century (GA21) Platform, Monash University Malaysia, Selangor, MalaysiaIntroduction: Schizophrenia (SCZ) is a highly debilitating disease despite its low prevalence. The economic burden associated with SCZ is substantial and mainly attributed to productivity loss. To improve the understanding of economic burden of SCZ in the low- and middle-income country regions, we aimed to determine the economic burden of SCZ in Malaysia.Methods: A retrospective study was conducted using a prevalence-based approach from a societal perspective in Malaysia with a 1 year period from 2013. We used micro-costing technique with bottom-up method and included direct medical cost, direct non-medical cost, and indirect cost. The main data source was medical chart review which was conducted in Hospital Kuala Lumpur (HKL). The medical charts were identified electronically by matching the unique patient’s identification number registered under the National Mental Health Schizophrenia Registry and the list of patients in HKL in 2013. Other data sources were government documents, literatures, and local websites. To ensure robustness of result, probabilistic sensitivity analysis was conducted.Results: The total estimated number of treated SCZ cases in Malaysia in 2015 was 15,104 with the total economic burden of USD 100 million (M) which was equivalent to 0.04% of the national gross domestic product. On average, the mean cost per patient was USD 6,594. Of the total economic burden of SCZ, 72% was attributed to indirect cost, costing at USD 72M, followed by direct medical cost (26%), costing at USD 26M, and direct non-medical cost (2%), costing at USD 1.7M.Conclusion: This study highlights the magnitude of economic burden of SCZ and informs the policy-makers that there is an inadequate support for SCZ patients. More resources should be allocated to improve the condition of SCZ patients and to reduce the economic burden.Keywords: economic burden, schizophrenia, Malaysia, cost of illness, lower-income countries, middle-income countries, societal perspective